STRUCTURE OF THE MANAGEMENT SYSTEM OF QUALITY OF ELECTRONIC LEARNING RESOURCES (Journal of Information Technologies in Education (ITE), 2011)
Results on designing and implementation of quality management system of electronic learning resources and its use for the organization and carrying out of quality monitoring of resources at university are presented. Distance learning system «Kherson Virtual University» is used as illustration of quality monitoring of electronic learning resources in Kherson State University.
Keywords: criteria of quality electronic learning resources; distance learning; metrics; quality control; quality management system; quality monitoring; types of learning resources